Sir3 mediates long-range chromosome interactions in budding yeast - Ruault, Myriam; Scolari, Vittore F.; Lazar-Stefanita, Luciana; Hocher, Antoine; Loïodice, Isabelle; Koszul, Romain; Taddei, Angela (Genome Research, 2021)
Physical contacts between distant loci contribute to regulate genome function. However, the molecular mechanisms responsible for settling and maintaining such interactions remain poorly understood. Here, we investigate the well-conserved interactions between heterochromatin loci. In budding yeast, the 32 telomeres cluster in 3–5 foci in exponentially growing cells. This clustering is functionally linked to the formation of heterochromatin in subtelomeric regions through the recruitment of the silencing SIR complex composed of Sir2/3/4. Combining microscopy and Hi-C on strains expressing different alleles of SIR3, we show that the binding of Sir3 directly promotes long-range contacts between distant regions, including the rDNA, telomeres, and internal Sir3-bound sites. Furthermore, we unveil a new property of Sir3 in promoting rDNA compaction. Finally, using a synthetic approach, we demonstrate that Sir3 can bond loci belonging to different chromosomes together, when targeted to these loci, independently of its interaction with its known partners (Rap1, Sir4), Sir2 activity, or chromosome context. Altogether, these data suggest that Sir3 acts as a molecular bridge that stabilizes long-range interactions.